2020
DOI: 10.7150/ijms.39432
|View full text |Cite
|
Sign up to set email alerts
|

Provoking factors for postpartum chronic hypertension in women with preceding gestational hypertension/preeclampsia: A longitudinal cohort study of 22,798 pregnancies

Abstract: Background: A proportion of women with pregnancies complicated by gestational hypertension/preeclampsia (GH-PE) will have persistent postpartum chronic hypertension (CHTN). Common risk factors for postpartum CHTN include older age, pre-existing CHTN, smoking, pre-pregnancy obesity (elevated BMI), and co-morbidities such as thyroid disorders. However, most of explored risk factors are pre-pregnancy factors, and were mainly based on studies with small sample size. Methods: To investigate provoking pre-pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…PE is the main cause of maternal and fetal mortality and morbidity (19,20). GDM complicated by PE further increases perinatal adverse events (21)(22)(23)(24), future maternal risk of chronic hypertension, cardiovascular disease, and diabetes (25)(26)(27); offspring body mass index (BMI) also steadily increases over time (28). Identifying factors associated with occurrence of PE in women with GDM, especially those that are controllable, is important for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…PE is the main cause of maternal and fetal mortality and morbidity (19,20). GDM complicated by PE further increases perinatal adverse events (21)(22)(23)(24), future maternal risk of chronic hypertension, cardiovascular disease, and diabetes (25)(26)(27); offspring body mass index (BMI) also steadily increases over time (28). Identifying factors associated with occurrence of PE in women with GDM, especially those that are controllable, is important for improving pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up of HDP patients for 5-21 years after delivery demonstrated that they had a four-fold higher risk of developing PHTN than those without HDP [ 6 , 8 , 21 ]. One-year follow-up studies showed that PHTN occurred in 17-29% of patients with PE after discharge and that the probability of postpartum CVD was significantly higher in the PE group than in those with normal pregnancies; among those with PE, the BP returned to normal [ 12 , 13 , 22 , 30 ]. The 13.4% incidence of PHTN among the 1,000 PE subjects here reflects the morbidity of persistent PHTN in Taiyuan City, Shanxi Province, China.…”
Section: Discussionmentioning
confidence: 99%
“…Current PE models mostly involve the early prediction of adverse pregnancy outcomes and long-term cardiovascular disease risk [ 19 21 ]. Prognostic data on BP profiles at short-term follow-up during the postpartum period in patients with PE are scarce, although some other risk factors of PHTN have been suggested, including preexisting hypertension before pregnancy and a higher body mass index (BMI) [ 11 ], older age, smoking, pre-pregnancy obesity, comorbidities such as thyroid disorders [ 12 ], and decreased serum placental growth factor [ 22 ]. Few studies to date have reported the clustered and combined effects of multiple risk factors on BP recovery during the 3-month or longer period after delivery in patients with PE.…”
Section: Introductionmentioning
confidence: 99%
“…2 Prior research has demonstrated that a substantial proportion of persons with preeclampsia will have persistent hypertension up to five years after delivery and long-term risk of developing chronic hypertension. 3,4 In these studies, associated risk factors for persistent hypertension included excessive gestational weight gain, presence of gestational diabetes mellitus, preeclampsia with severe features, dyslipidemia and age greater than 40. [4][5][6] Identifying modifiable risk factors for persistent hypertension may help to reduce long-term consequences and the associated health burden of postpartum preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In these studies, associated risk factors for persistent hypertension included excessive gestational weight gain, presence of gestational diabetes mellitus, preeclampsia with severe features, dyslipidemia and age greater than 40. [4][5][6] Identifying modifiable risk factors for persistent hypertension may help to reduce long-term consequences and the associated health burden of postpartum preeclampsia.…”
Section: Introductionmentioning
confidence: 99%